Biotechnological fixes and the Big Three urgent moral challenges facing the global livestock industry - Shriver, Adam J. (Frontiers in Animal Science, 2024)
The current global food system, and in particular the livestock industry, has been effective at providing low-cost calories to large segments of the population, but it also causes significant harms and poses serious risks. In particular, the global food system currently likely causes billions of animals to suffer every year, significantly contributes to climate change, and threatens public health via the possibility of zoonotic disease. There are many other problems that have been identified with the livestock industry, but these three threats, which I refer to as the Big Three, are among the most urgent moral issues in the world. Significant progress could be made to address all three of these risks if the global population moved to a primarily plant-based diet. However, there are reasons to believe this possibility is unrealistic given current consumer preferences and political realities. As an alternative, one could ask whether an approach relying entirely on novel biotechnology could be used to address the urgent moral challenges of the global livestock industry without substantially changing the consumer experience or facing political backlash. In this paper I consider what such a scenario would look like, and argue that failing to address any one of these three major issues would be a serious moral failing. Though many other suggestions have been made looking at how biotechnology might address individual issues, this paper suggests that in order to avoid the need for difficult behavioral and political changes, biotechnological solutions would ultimately need to be developed that address welfare, environmental, and public health concerns.